2013
DOI: 10.1111/geb.12087
|View full text |Cite
|
Sign up to set email alerts
|

Testing instead of assuming the importance of land use change scenarios to model species distributions under climate change

Abstract: Aim Species distribution models often assume a changing climate (dynamic climate variables) but unchanged land use (static land use variables) to estimate future species distribution shifts. However, scenarios of projected land use change are available to calculate dynamic land use variables. Surprisingly, the importance of using dynamic instead of static land use variables when projecting potential future species distributions under climate change remains largely unexplored. We tested whether the joint inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 50 publications
3
76
0
Order By: Relevance
“…Therefore, considering the importance of geophytes for the existence of Merodon species at the larval stage as well as the richness and abundance of floral resources for the adults, the inclusion of land cover change could be more informative, resulting in a more integrated knowledge of hoverflies potential future distribution shifts. However, Martin et al (2013) found that the incorporation of land cover change scenarios did not contribute significantly to the assessment of species' future distribution ranges. Although they were not discarding their future use, they indicated the necessity of an improvement of the thematic resolution of land cover change scenarios.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, considering the importance of geophytes for the existence of Merodon species at the larval stage as well as the richness and abundance of floral resources for the adults, the inclusion of land cover change could be more informative, resulting in a more integrated knowledge of hoverflies potential future distribution shifts. However, Martin et al (2013) found that the incorporation of land cover change scenarios did not contribute significantly to the assessment of species' future distribution ranges. Although they were not discarding their future use, they indicated the necessity of an improvement of the thematic resolution of land cover change scenarios.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have compared the effects of using explanatory variables with a range of thematic and spatial resolutions in species distribution modelling and showed that they have a large effect on predictive accuracy [75,76]. In particular Liang et al [77] modelled three thematic and six spatial resolutions and assessed individual effects and interactions.…”
Section: Recent Progress (Post-2010) In Research On the Effects Of Spmentioning
confidence: 99%
“…Information on the Earth's surface such as land cover and related environmental processes is of 29 great importance for a plethora of applications, for example for decision-making on issues related 30 to agriculture and food security (Fritz et al, 2013;Gardi et al, 2015), monitoring the distribution 31 of species (Martin et al, 2013;Tuanmu and Jetz, 2014), and modelling of the Earth's climate 32 (Luyssaert et al, 2014;Mahmood et al, 2014). For this reason, thematic mapping through a 33 classification analysis is a very common application of remote sensing.…”
Section: Introduction 28mentioning
confidence: 99%